2017
DOI: 10.1177/0954408917717994
|View full text |Cite
|
Sign up to set email alerts
|

Investigation the mechanical, rheological, and morphological properties of acrylonitrile butadiene styrene blends with different recycling number content

Abstract: In this study, acrylonitrile butadiene styrene polymer was exposed to 12 injection cycles to investigate the influence of recycling number on the mechanical, rheological, and morphological properties. Also, binary and ternary blends including different weight percentages and recycling number of virgin-recycled polymers were prepared. A slight decrement was found in the tensile strength values with recycling number. All blends including recycled polymer (binary or ternary) gave lower tensile strength values wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 31 publications
3
8
0
Order By: Relevance
“…This is so-called primary recycling. The recycled polymer is, of course, not or slightly degraded and the properties of this monopolymer blend are certainly still good [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. However, in general, low amounts of recycled polymer are usually mixed with the virgin polymer because, at least in some cases, increasing its content, the properties of the blend, and in particular the elongation at break, dramatically decay.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is so-called primary recycling. The recycled polymer is, of course, not or slightly degraded and the properties of this monopolymer blend are certainly still good [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. However, in general, low amounts of recycled polymer are usually mixed with the virgin polymer because, at least in some cases, increasing its content, the properties of the blend, and in particular the elongation at break, dramatically decay.…”
Section: Introductionmentioning
confidence: 99%
“…More recent studies [12][13][14][15] reported results on virgin-recycled ABS blends. Melt flow data indicated that all blends containing recycled material showed higher melt flow index values as compared to virgin polymer.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous works, we have investigated the rheological and mechanical properties of monopolymer blends of high-and low-density polyethylene [1,2] as well as polypropylene [3,4], polyvinylchloride [5], polyethylenetherephthalate [6] and polyamide [7]. Similarly, other research groups have examined monopolymer blends of virgin and recycled acrylonitrile-butadiene-styrene (ABS) [8][9][10][11], high density polyethylene (HDPE) [12,13] and polyethylene terephthalate (PET) [14][15][16]. The different degradation processes occurring in the recycled polymer influence the properties of their blends and alter their compatibility to a certain extent.…”
Section: Introductionmentioning
confidence: 99%
“…They prepared binary and ternary blends containing different weight percentages of virgin and recycled polymers. They found that the impact strengths of the blends with recycled ABS were lower than the impact strength of virgin ABS [14].…”
Section: Introductionmentioning
confidence: 99%